Nanomaterials in the diagnosis and therapy of osteoarthritis: current research advances and future clinical prospects - Li, Xin; Shen, Zeyan; Zhang, Songou; Chen, Yuke; Lu, Xuanyuan; Hu, Xujun (Frontiers in Bioengineering and Biotechnology, 2025)
Osteoarthritis (OA), the most prevalent degenerative joint disorder, is characterized by progressive cartilage degradation, synovial inflammation, and functional impairment. Current treatments mainly alleviate symptoms without halting disease progression, and systemic drug administration often leads to poor absorption, short half-life, off-target effects, and adverse reactions. Recent advances in nanotechnology provide innovative solutions through nanomaterials with superior physicochemical properties, enabling targeted delivery, sustained release, and reduced toxicity. Compared with conventional therapies, nanotherapeutic strategies enhance treatment efficacy, support cartilage regeneration, and offer diagnostic potential. This review summarizes recent progress in nanomaterials for OA therapy, including liposomes, polymeric and inorganic nanoparticles, exosomes, gene delivery systems, and multifunctional platforms. We highlight their mechanisms, advantages, limitations, and translational potential, aiming to provide a comprehensive reference for future nanomedicine development in OA treatment.